Transendensi Batas Sosial dan Religius dalam Yohanes 4: Telaah Teologis atas Sikap Kristus sebagai Penuai Jiwa - Putra, Henry Ekacahya (STT Pelita Dunia, 2025)
This study analyzes the passage of John 4:1–42 to explore how Christ transcends social, cultural, and religious boundaries through his encounter with the Samaritan woman. The phenomenon of exclusivity in the lives of believers that hinders the church's mission is the main background of this study. Using qualitative theological methods with exegetical and narrative hermeneutic approaches, the study aims to uncover the theological meaning of Christ's inclusive actions and their relevance for contemporary cross-cultural ministry. The results show that Jesus' interactions are a theological statement of God's transcendent and universal love, which transcends ethnic, gender, and doctrinal barriers. The novelty of this study lies in the interpretation of Christ as the